Public confidence in the judiciary: the interaction between political awareness and level of democracy. Issue 4 (6th June 2016) - Aydın Çakır, Aylin; Şekercioğlu, Eser
Abstract : Apart from the studies that focus on public attitudes toward higher courts in advanced democracies, we know little about the factors that can explain public confidence in the judiciary in a comparative setting. In this regard, the goal of this study is to explain whether, and to what extent, the country's level of democracy moderates the impact of political awareness on public confidence in the judiciary. This study uses hierarchical linear models to analyse the interaction between individual and country level factors by using the World Values Survey (2005–2009) data for 49 countries and various other data sources. Our empirical results show that in advanced democracies political awareness variables like education and political participation have a positive impact on public confidence in the judiciary, whereas in countries with weak levels of democracy higher political awareness leads to increased cynicism about the judiciary. These results suggest that a one-size-fits-all approach to explain confidence in the judiciary is not possible when we are dealing with a wide range of societies that vary in terms of many characteristics, both institutional and cultural.